Editorial Policy - Della Casa , Dra. Romina (Antiguo Oriente, 2025)
Antiguo Oriente is the scholarly journal of the Centro de Estudios de Historia del Antiguo Oriente (Institute of Studies for the History of the Ancient East), History Department, School of Social, Pontifical Catholic University of Argentina. It will consider for publication original manuscripts related to the history of the societies of the Ancient Near East and the Eastern Mediterranean from the Paleolithic through the Roman-Hellenistic period. It is published once a year. Antiguo Oriente publishes articles and book reviews in Spanish, French or English. Papers which do not take into account the instructions for contributors will not be accepted.